Construction of an impulse current generator prototype applied in electrical grounding systems - Ferraz, Rafael; Oliveira, Sostenes; Silva, Alan; Nerys, Jose; Alves, Aylton; Calixto, Wesley (2015 CHILEAN Conference on Electrical, Electronics Engineering, Information and Communication Technologies (CHILECON), 2015)
This paper presents a device that is able to reproduce atmospheric discharges in a small scale. First, there was simulated an impulse generator circuit that could meet the main characteristics of the common lightning strokes waveform. Later, four different generator circuits were developed with the selection made by a microcontroller. Finally, the output was subject to amplification circuits that increased its amplitude. The impulses generated had a very similar shape compared to the real atmospheric discharges to the international standards for impulse testing. The apparatus is meant for application in electric grounding systems and for tests in high frequency to measure the soil impedance.